Folate (vitamin B9) content analysis in bread wheat (Triticum aestivum L.) - Zheng, Jun; Wang, Xingsu; Wu, Bangbang; Qiao, Ling; Zhao, Jiajia; Pourkheirandish, Mohammad; Wang, Juanling; Zheng, Xingwei (Frontiers in Nutrition, 2022)
Vitamin B9, particularly folic acid, is an essential molecule for human health. Wheat flour is one of the major sources of calory intake by humans. The selection of folate-rich genotypes in wheat breeding can enhance the natural folate value in the daily diet. This study used a precise, high-performance liquid chromatography (HPLC) assay to analyze folate content in a 262-accession Chinese wheat mini-core collection (MCC) grown in three environments. Four folate derivatives in grains, including tetrahydrofolate (THF), 5-methyltetrahydrofolate (5-CH3-THF), 5-formyltetrahydrofolate (5-CHO-THF), and 5,10-methenyltetrahydrofolate (5,10-CH+THF) were considered. An association analysis of water regimes, accession types, released years, geographical origin, and agronomic traits with folate content was conducted for the first time. There was a large amount of variation in folate content in the analyzed accessions, with genotype identified as the main influencing factor. Total folate content was significantly correlated with content of the four MCC derivatives within three environments. 5-CH3-THF and 5-CHO-THF were the most abundant among the four folate derivatives and were positively correlated with high folate content. The twelve accessions with the highest folate content showed an average of more than 80 µg/100 g. The analysis demonstrated that this Chinese wheat had not undergone extensive selection for folate content during breeding, which is unrelated to the geographical origin, accession types, winter/spring types, and grain colors of wheat. The content of THF, 5-CH3-THF, and 5,10-CH+THF was significantly negatively correlated with grain width, grain thickness, and thousand kernel weight. A relatively weak negative relationship manifested between folate contents and flowering date, whereas no significant correlation with tiller number, grain number per spike, maturity date, height, and spike length was detected. The investigation benefits wheat breeders for folate enhancement.